MODERN IMAGING APPROACHES IN THE EVALUATION OF ODONTOGENIC SINUSITIS - GAVRIL LIVIU-CIPRIAN; GAVRIL ROXANA-FLORENTINA; ȚEPORDEI RĂZVAN TUDOR; MAXIM RĂZVAN RADU; MORARU MARIUS CONSTANTIN; PĂUNA ANA MARIA; LUDUȘANU ANDREEA; STĂTESCU GABRIEL (Romanian Journal of Oral Rehabilitation)
Odontogenic sinusitis (OS) is a form of maxillary sinus inflammation originating from dental pathologies, such as periapical lesions, periodontal disease, or complications following dental procedures. Accurate diagnosis is critical for effective treatment and prevention of chronic complications. Over the past decade, advancements in imaging modalities have revolutionized the diagnostic approach to OS, providing enhanced visualization of the maxillary sinus and its relationship with dental structures. This paper reviews modern imaging techniques, including panoramic radiography, cone-beam computed tomography (CBCT), multidetector computed tomography (MDCT), and magnetic resonance imaging (MRI), highlighting their respective roles, advantages, and limitations in the evaluation of OS. Among these, CBCT has emerged as the gold standard for its high resolution and three-dimensional visualization of the tooth-bone-sinus complex, offering unparalleled accuracy in identifying odontogenic causes of sinusitis. MDCT remains a valuable tool for broader evaluations, particularly in cases involving extensive sinonasal involvement. MRI, while limited in assessing bony structures, provides superior soft tissue contrast and is particularly useful in identifying mucosal inflammation or complications extending beyond the maxillary sinus. The paper emphasizes the importance of selecting the appropriate imaging modality based on clinical presentation and suspected pathology. By integrating advanced imaging techniques into the diagnostic process, clinicians can achieve more precise identification of odontogenic aetiologies, optimize treatment planning, and improve patient outcomes. Future research should focus on refining imaging protocols and exploring novel technologies to further enhance diagnostic accuracy and patient care.